Whither Europe?: Postcolonial versus Neocolonial Cosmopolitanism - Bhambra, Gurminder K. (Interventions (London, England), 2016)
The financial collapse of 2008, and its consequences of recession in the Eurozone and beyond, has exacerbated tensions at the heart of the postwar European project. The politics of austerity has provoked populist and far-right political responses, scapegoating migrants and minorities and increasingly calling the project of integration into question. In this essay I focus on responses by social theorists to the emerging crisis. In particular, I address the contrast between their reaffirmation of 'European' cosmopolitanism and their associated criticisms of multiculturalism, which, instead, is posed as a threat. In this way, while they challenge those who wish the dissolution of the European project, they do so at the expense of those seen to be internal 'others', whose scapegoating is one aspect of the populist threat to that integration. It is their failure to address the colonial histories of Europe, I argue, that enables them to dismiss so easily its postcolonial and multicultural present. As such, they reproduce features of the populist political debates they otherwise seek to criticize and transcend. A properly cosmopolitan Europe, I suggest, would be one which understood that its historical constitution in colonialism cannot be rendered to the past by denial of that past.